Nobelova nagrada za fiziko 2014 in revolucija v osvetljevanju - Zgonik, Marko (Obzornik za matematiko in fiziko, 2014)
Isamu Akasaki and Hiroshi Amano from Nagoya University and Shuji Nakamura, formerly from a Japanese company Nichia Chemicals, at present a professor in the U.S.A., were awarded the 2014 Nobel Prize in Physics. The article describes the pathway to the invention of blue LED based on GaN. Fluorescent conversion of the blue emission into the white light makes blue LEDs especially versatile. The new white light source is effcient, durable and environmentally friendly.
Keywords: fizika; physics; Nobelove nagrade; Modra LED; modra LED dioda; LED sijalka